Sosialisasi Keamanan Siber untuk Pelajar: Upaya Meningkatkan Literasi Digital di Era Modern - Muhammad Al Makky; Nicholas Efesus Barus; Chelsea Georgia Sevilla Wonmaly; Muhammad Roghib Roghib; Yerick Rafaldy De Fretes; Muhammad Faris Fathoni (MATRADIPTI, 2024)
Kegiatan